Permanence of professionals who work in the Tuberculosis Control Program - Danielle Galdino de Paula; Alexandre Sousa da Silva; Tereza Cristina Scatena Villa; Maria Catarina Salvador da Motta
ABSTRACT Objective: To analyze the length of stay of the professionals who work in the Tuberculosis Control Program in Basic Health Units of the city of Rio de Janeiro/RJ. Method: Sectional study, developed in eight Health Units of the Maré Complex/RJ. Physicians, nurses, nursing technicians and Community Health Agents of the Family Health Teams were interviewed. The Kruskal-Wallis test was used to verify the existence of groups with the same distribution, and Dunn's multiple comparison test with Bonferroni correction, to identify which group presented a difference. Results: Among Health Units, a significant difference was observed in the length of work (p-value = 0.0005909) and in the dwell time (p-value = 0.0003598). Conclusion: It was observed low length of stay of the professionals that work in the Basic Health Units. This result points to challenges inherent in the control of tuberculosis at the local level.